2005
DOI: 10.1017/s1355617705050083
|View full text |Cite
|
Sign up to set email alerts
|

Standard regression-based methods for measuring recovery after sport-related concussion

Abstract: Clinical decision making about an athlete's return to competition after concussion is hampered by a lack of systematic methods to measure recovery. We applied standard regression-based methods to statistically measure individual rates of impairment at several time points after concussion in college football players. Postconcussive symptoms, cognitive functioning, and balance were assessed in 94 players with concussion (based on American Academy of Neurology Criteria) and 56 noninjured controls during preseason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
258
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 313 publications
(273 citation statements)
references
References 43 publications
11
258
3
1
Order By: Relevance
“…Although available findings to date suggest that injury severity (mild, moderate, severe), more than injury mechanism (blast-associated vs. not), is the greater determinant of cognitive outcomes in OEF/OIF TBI samples (Belanger et al, 2009), the reality is that the natural history of BRC has yet to be established. Until longitudinal examination of neuropsychological performances is conducted on a much larger scale and with much larger OEF/OIF samples, as has been conducted in sports concussion samples (e.g., McCrea et al, 2005), the nature of cognitive recovery following BRC will remain unclear. For now, paired with the findings of other research groups (Brenner et al, 2010;Nelson et al, 2009), present findings suggest that blast-related MTBI does not typically result in chronic objective cognitive impairments.…”
Section: Discussionmentioning
confidence: 99%
“…Although available findings to date suggest that injury severity (mild, moderate, severe), more than injury mechanism (blast-associated vs. not), is the greater determinant of cognitive outcomes in OEF/OIF TBI samples (Belanger et al, 2009), the reality is that the natural history of BRC has yet to be established. Until longitudinal examination of neuropsychological performances is conducted on a much larger scale and with much larger OEF/OIF samples, as has been conducted in sports concussion samples (e.g., McCrea et al, 2005), the nature of cognitive recovery following BRC will remain unclear. For now, paired with the findings of other research groups (Brenner et al, 2010;Nelson et al, 2009), present findings suggest that blast-related MTBI does not typically result in chronic objective cognitive impairments.…”
Section: Discussionmentioning
confidence: 99%
“…The SAC is likely to identify the presence of concussion in the early stages postinjury (sensitivity 80%-94%, specificity 76%-91%) (multiple Class III studies). 8,25,26,[34][35][36][37] Neuropsychological testing. Instruments for neuropsychological testing are divided into 2 types on the basis of their method of administration: paper-and-pencil and computer.…”
mentioning
confidence: 99%
“…9 This metabolic disruption lasts about a week, mirroring the timeline of clinical symptom recovery. 10,11 In animal models, researchers 12 have demonstrated that a second concussion during this period of brain vulnerability creates greater metabolic and cognitive impairment for a longer time. Similar findings of vulnerability and impaired recovery have also been shown in male athletes.…”
mentioning
confidence: 99%